Study of Faunal Diversity of Laxmipur Pond at Raxaul Area of Indo-Himalayan Range of Bihar - Roy, Mandip Kumar; Deo, Amaresh Kumar; Rani, Akriti (International Journal of Applied Sciences and Biotechnology, 2014)
North Bihar exhibits a wide range of wet lands and net of water bodies due to its geographical distribution and climatic condition and has become a good source of income through fish culture and variety of important cultivable crops. The fish collected from water body are represented by 8 orders and 12 families, 18 genera and 23 species. During the entire period of investigation, altogether 32 genera of phytoplankton consisting of chlorophyceae, cyanophyceae, euglenophyceae and bascillariophyceae, etc. In the present study, Zooplankton are represented by 05 genera of 7 copepoda, 06 genera of ostracoda. The density of phytoplankton was found to be higher than Zooplankton. The population of plankton was observed to be low during rainy season. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.10003 Int J Appl Sci Biotechnol, Vol. 2(1): 93-96